PENGARUH INTENSI MELAKUKAN KECURANGAN TERHADAP PERILAKU KECURANGAN AKUNTANSI DENGAN MODERASI TEKNOLOGI INFORMASI - Mas’udah, Alysia Lailatul; Aulia, Yoosita (JEB17 : Jurnal Ekonomi dan Bisnis, 2026)
Abstract This study aims to analyze the influence of accounting fraud intentions on accounting fraud, with information technology as a moderating variable at SPX Express Hub Pabean Cantikan Surabaya. This study used a quantitative approach with primary data obtained through questionnaires distributed to 80 respondents. The data analysis methods used were multiple linear regression and moderated regression. Prior to hypothesis testing, the data were examined through validity, reliability, and classical assumption tests. The results showed that accounting fraud intentions and information technology had no significant effect on accounting fraud. Furthermore, information technology was unable to moderate the influence of accounting fraud intentions on fraudulent behavior. These findings indicate that accounting fraud is more influenced by factors other than the research variables. Keywords: fraud intention, accounting fraud, fraudulent behavior, information technology, moderation